A novel approach to estimate power demand of auxiliary engine loads of light duty vehicles - Gajanayake, Surath; Bandara, Saman; Sugathapala, Thusitha (Frontiers in Mechanical Engineering, 2023)
On par with the rapid motorization, excessive energy demand and air pollution have become major challenges in the global context. Fuel economy programs and emission reduction targets have proven to be among the most effective in mitigating these issues. In developing fuel economy related programs and policies, understanding the factors affecting the fuel consumption of road vehicles is essential. During the study the scope is limited to light duty vehicles. The auxiliary engine loads are one of the essential factors affecting a vehicle’s performance pertaining to fuel economy. An auxiliary engine load can be defined as the energy utilized to operate auxiliary equipment which draw power from the respective engine.. During the study, an analytical method is adopted to assess the impact of the engine auxiliary loads in terms of air-conditioning load, alternator load, water-pump and steering pump load. The study portrays a novel approach for estimating and modelling the air-conditioning load which is the major contributor in terms of energy consumption. As the main deliverables of the study, it is portrayed that an average car of 100 bhp (74.7 kW) of brake power, consumes approximately 12.770 kW of power for the functionality of engine auxiliary equipment at an operating engine speed of 3,000 RPM, which closely account for 17.1% of the total engine brake power output. It’s conspicuous that the major contributors towards the engine power demand are air-conditioning unit and the alternator unit, accounting for a substantial portion of over 97% of the total auxiliary power requirement, whereas the water-pump and the power steering-pump are accountable for a minimal power demand of 3% of the total auxiliary power demand.